2016
DOI: 10.3390/nu8100663
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Lipids Levels in Blood and Risk of Age-Related Macular Degeneration

Abstract: Lipid metabolism may be involved in the pathogenic mechanism of age-related macular degeneration (AMD). However, conflicting results have been reported in the associations of AMD with blood lipids. We performed a meta-analysis including a total of 19 studies to evaluate associations between blood lipids and this disease. The result reported that the high level of high-density lipoprotein cholesterol (HDL-C) obtained with an increment of 1 mmol/L could result in a significantly increase in the AMD risk of appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 47 publications
4
40
0
1
Order By: Relevance
“…Meanwhile, OX-LDL stimulation disrupts RPE barrier and induces VEGF/PDGF secretion in ARPE-19 cells, which further indicates the pathogenic mechanism of lipid oxidation to exudative AMD. Clinical trials have revealed the association between serum lipid levels and AMD [ 32 ]. However, little is known about oxidative damage of OX-LDL to CNV pathology in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, OX-LDL stimulation disrupts RPE barrier and induces VEGF/PDGF secretion in ARPE-19 cells, which further indicates the pathogenic mechanism of lipid oxidation to exudative AMD. Clinical trials have revealed the association between serum lipid levels and AMD [ 32 ]. However, little is known about oxidative damage of OX-LDL to CNV pathology in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Statins (e.g., atorvastatin and lovastatin), common cholesterol-lowering medications, are inhibitors for 3-hydroxy-3-methylglutaryl coenzyme A reductase, and have recently been reported to be useful for decreasing the risk of wet-type AMD [44] . Statin-induced decrease in serum low-density lipoprotein (LDL) cholesterol might reduce LDL cholesterol deposits in the drusen, which plays a key role in the pathogenesis of AMD [45] . In addition to lipid-lowering effects, statins also exert anti-inflammatory effects through inhibition of the inflammatory pathway [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that HDL is involved in pro-inflammatory as well as complement inhibitory tasks. Higher HDL levels may cause imbalance of the physiological homeostasis 8,63 . Taken together, this plethora of biological leads supports the contention that HDL may play a role in the initiation of AMD.…”
Section: Accepted Manuscriptmentioning
confidence: 99%